The Nexus Between Human Resource Management Practices and Innovation Performance in Organizations - Ismail, Fadillah; Bano, Yasmeen (JBS Nexus, 2024)
Striving for competitiveness in the marketplace drives enterprises to view human capabilities as critical assets for achieving excellent organizational innovation performance. This study investigates the relationship between human resource management practices and organizational innovation performance. Previous studies focused on four main HRM components: recruitment and selection, training, performance appraisal, compensation, This quantitative study utilized a survey instrument distributed online to SMEs located at Selangor and Kuala Lumpur. The respondents included 105 individuals working at various managerial levels in these organizations. Data analyses were conducted using SPSS software version 22. The findings revealed that recruitment and selection, training, and compensation significantly influence organizational innovation performance, while performance appraisal, employee participation, and career development showed no significant impact. To boost organizational innovation performance , enterprises should recruit individuals with relevant skills, implement robust selection and training programs, establish a fair compensation system that rewards innovation, re-evaluate performance appraisals to align with innovation goals, and promote employee participation and career development.